Insulin-like growth factor I stimulates erythropoiesis in hypophysectomized rats. - Kurtz, A (1988)
Stimulation of erythropoiesis during growth is necessary to ensure proportionality between erythrocyte mass and body mass. However, the way by which erythrocyte formation is adapted to body growth is still unknown. Growth arrest in hypophysectomized rats is accompanied by decreased erythropoiesis. We have, therefore, examined whether insulin-like growth factor I (IGF-I), the mediator of growth hormone effects on body growth, is able to restore erythropoiesis in these animals. Subcutaneous infusions of 120 micrograms of recombinant human IGF-I per day in hypophysectomized rats led to increases in body weight, 59Fe incorporation into erythrocytes, and the number of reticulocytes that were similar to increases caused by infusions of 28 milliunits of human growth hormone per day. Body weight gain and 59Fe incorporation were linearly correlated. Like growth hormone, IGF-I also caused a significant rise in serum erythropoietin concentrations. However, the stimulatory effect on erythropoiesis occurred before serum erythropoietin levels had risen. These results demonstrate that IGF-I mediates the stimulatory effect of growth hormone on erythropoiesis in vivo and thus further support the somatomedin concept. They also show that IGF-I can stimulate erythropoiesis in an endocrine manner, and they suggest two possible routes of action: a direct one and an indirect one by means of enhanced erythropoietin production.